Never blow a kiss - Lovise, Lindsay (Lovise, Lindsay. Secret Society of Governess Spies., 2024)
"The utterly charming Emily Leverton has a dark past and is determined to leave it behind in her respectable new role as a governess. But when she is recruited by a secret network of governesses who spy on the ton, it may just be a way to redeem the dark secrets of her past. Straddling the worlds of the ton and the working class, as an ex-solider turned railroad magnate, Zach hunts killers for the Metropolitan Police by day and dutifully attends balls at night. In neither world has he met a woman with the brazenness to mock him. So when a saucy governess blows him a kiss he is determined to catch her, never expecting that when he does he will find an intelligent, quirky woman hiding more than her true name. As Zach peels back the layers of Emily's lies, he falls for the street-wise woman who handles a dagger like a pro and kisses like a mistress. But when his affair with Emily intertwines with his hunt for a killer, he discovers Emily is hiding an explosive secret--one that could destroy them both"--